Implementation of One-Stop Services Policy (PTSP) in North Jakarta City, DKI Jakarta Province - Mary Ismowati; Ahmad Hidayat Rahadian; Muhammad Ali Massyhury; Muhammad Rafi Suryadi (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
The aim of the study was to obtain a formulation of the implementation of the One-Stop Services Policy (PTSP) in the North Jakarta Administrative City, namely the implementation of Perda No. 12 of 2013, and the Implementation of Presidential Regulation No. 91 of 2017 concerning the acceleration of ease of doing business through the implementation of an information technology-based licensing system (OSS). The research method used a qualitative approach by conducting interviews with a number of informants to determine the conditions and phenomena of the implementation of PTSP policies in North Jakarta. The research involved two research members from students in the framework of thesis research. The results of the research show that implementers have understood their duties and functions, but in the smooth running of their duties, they are constrained by a lack of human resources both in quantity and quality, support for information technology equipment that is not up to date, including the availability of information technology personnel at the district and sub-district levels. Then the OSS policy according to PP No. 24/2018 has not been fully effective, because it has not been fully integrated with the existing licensing system in PM-PTSP DKI Jakarta, namely JakEVO. The main obstacle to policy implementation, namely in terms of human resources, employee status has not been transferred to functional positions so that it affects career ranks and motivation. In addition, there is no HR competency standard for services, for online system services are not implemented according to target. The solution to overcome the obstacles conceptually has not been done.